Topical pharmaceutical formulations for irradiated skin care - Milutinov, Jovana; Pavlovic, Nebojsa (PONS - medicinski časopis, 2023)
Radiotherapy as the application of ionizing radiation is one of the main current therapeutic modalities for cancer. However, one of the most frequent adverse effects of this therapeutic strategy is radiodermatitis, which significantly affects quality of patients’ lives. Nowadays, there is no consensus on the appropriate therapy of radiodermatitis, however there are basic recommendations that should be followed. The aim of this study was to make a review of current recommendations during radiotherapy for the prevention of radiodermatitis through application or avoidance of application of certain topical pharmaceutical formulations. Most studies proposed the adequate personal hygiene as a general preventive measure. Basic recommendations also include wearing loose-fitting clothing, using an electric shaver, sunscreens, moisturizers, and avoiding alcohol and cigarettes. According to the Multinational Association of Supportive Care in Cancer (MASCC), the only recommendation for the prevention and treatment of radiodermatitis is gentle washing using mild soap, as well as the use of topical steroids and silver sulfadiazine. Some studies report the possibility of using photobiomodulatory therapy in the prevention of radiodermatitis, as well as non-corticosteroid creams based on aloe, hyaluronic acid, calendula and comfrey. The use of comedogenic topical preparations, those containing alcohol, benzoyl peroxide and/or alpha-hydroxy acids, as well as those containing potential contact allergens and irritants, should be avoided. Adequate guidelines supported by strong evidence and consensus do not exist, and many recommendations were later refuted. Therefore, further research in this field is necessary to find a satisfying solution for an issue of radiation dermatitis.